What makes an online consumer review trustworthy?. (May 2016) - Filieri, Raffaele
Graphical abstract: Highlights: Explores how consumers process information from online consumer reviews. Explores how consumers assess trustworthiness of online consumer reviews. Based on interviews with 38 users of online reviews having various backgrounds. Develops a new theoretical framework to explain perceived review trustworthiness. Abstract: Online consumer reviews (OCRs) are increasingly used by consumers to make informed decisions about tourism-related products. However, there is an increase in concern about the level of trustworthiness of OCRs. As yet, little is known about how consumers assess trustworthiness and untrustworthiness of OCRs. This study aims to fill this gap by using a grounded theory approach based on 38 interviews with users of OCRs. Results show that consumers primarily use cues related to the message content and style and review extremity and valence to assess trustworthiness. Findings indicate that moderating variables such as consumer involvement and experience as well as the type of website affects the way consumers assess trustworthiness. Reviews perceived as untrustworthy are discounted by consumers.